Special Issue: Avian Adenoviruses - Anna Schachner; Michael Hess (Viruses, 2022)
For years, research on avian adenoviruses, here fowl adenoviruses (FAdVs), received less attention, mainly due to limited clinical relevance in poultry production [...]